Optimization of Screen in a Water Chestnut Decorticator - Alam, MD.Shafiq; Singh, D S; Seghal, V K (Journal of Agricultural Engineering, 2001)
A power operated water chestnut decorticator based on groundnut decorticator design was tested and evaluated. Screens with different percentages of perforation area (20.56%, 26.75%, 30.88%, 38.07%, 41.16%) were fabricated and tested by decorticating water chestnut at 9.95 per cent moisture content (d.b). Optimum screen was found to have 38.07 percent perforation area on the basis of shelling coefficient, decortication efficiency and specific energy requirement.